An analysis of ocular features and vision loss at presentation and after treatment in systemic lupus erythematosus in 60 patients - M. Shantha, Sruthi; Annamalai, Radha; Muthayya, Muthukumar (International Journal of Medical Research and Review, 2016)
Introduction: Systemic lupus erythematosus (SLE) is a chronic, inflammatory, multisystem autoimmune disease and ocular involvement occurs in several forms. It may be the first indicator of underlying SLE. Early identification and precise treatment of the disease can reduce blindness. The objective of this study was to analyze the causes of visual loss before and during treatment. Methods: This is a retrospective cohort study on 60 patients over 2 years in multispecialty, tertiary eye care hospital. Ophthalmic examination and routine and ancillary investigations were performed. Patients were followed up for at least one year to assess the progress of ocular features, their response to treatment and development of complications. Case records from a referral practice in patients with systemic lupus erythematosus, with diagnosis of dry eye, peripheral ulcerative keratitis, episcleritis, scleritis, uveitis, retinitis or optic neuropathy were analyzed. Results: In our study, the incidence of episcleritis was most frequent followed by dry eye, retinopathy and keratitis. Age group affected was 34 to 52 years and more in women. Scleritis was associated with decreased vision and maximum complications. Following treatment, cataract was the commonest cause of blindness. Conclusion: Our study showed the presence of simultaneous, multiple ocular complications which make treatment and follow up very crucial to avoid blindness. Ocular signs that occurs in SLE can be vision threatening and requires immediate assessment and management by an ophthalmologist. Drugs used to treat SLE may also cause blindness and coordinated treatment between rheumatologist, physician and ophthalmologist needs to be adopted.